STUDI PENGGUNAAN PASIR LAUT SEBAGAI FILLER PADA CAMPURAN ASPHALT CONCRETE BINDER COURSE (AC-BC) - Jaya, Trio Mareta; Bahri, Samsul; Razali, Makmun Reza (Universitas Bengkulu, 2018)
This research is a new innovation to find alternative material to replace Portland cement filler by using sea sand. This study examined the effect of sea sand usage on Asphalt Concrete Binder Course (AC-BC) mixture with sea shifting variation of 25%; 50%; 75%, and 100%. This research is an experimental study in laboratory by using Marshall test method in the form of stability, melting, Marshall quotient (MQ), VMA, VFA, and VIM. To support the test results conducted in the laboratory research including physical examination of asphalt, aggregate, and filler. The results of this study obtained the value of Marshall characteristics for the best VMA is at 100% variation of 16.89%; The highest VFA value at 100% variation of 81,78%; The best VIM values are at normal conditions of 4.10%; The best density value in normal condition is 2.35 T/m³; The highest stability value under normal conditions of 1519.23 kg; The best flow rate is in the 25% variation of 4.52 mm; The highest MQ values are in normal condition of 453.21 kg/mm. The use of sea sand as filler in all variations can be used although not all Marshall characteristic variables are high in value compared with normal conditions without replacement. The more sea sand used as filler, the more asphalt content needed in a mixture, in this study the asphalt content increased 2% when compared with the condition without change